PENGARUH ANALISIS JABATAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT THAMRIN BROTHERS CABANG BATURAJA 1 - Rini Apriyani (KOLEGIAL, 2017)
The purpose of this study is to determine the effect of job analysis and compensation on employee performance at PT Thamrin Brothers Branch Baturaja 1. The sampling technique using the technique of Disproportionate Stratified Random Sampling where sampling of members of the population randomly and stratified but members of the population is hiterogen (not similar ). The sample in this research is obtained 52 employees. The result of this research shows that job analysis has influence to employee performance with correlation coefficient value is 0,778 and compensation has influence to employee performance with correlation coefficient value is 0,684. Multiple correlation coefficient R equal to 0,812 which mean have strong influence between job analysis and compensation on employee performance at PT Thamrin Brothers Baturaja Branch 1. Multiple regression equation Y = 10,586 + 0,558X1 + 0,228X2 + Et, with t test can be concluded that analysis Position and compensation jointly both have a significant influence on employee performance at PT Thamrin Brothers Baturaja Branch.